PROFIL PESERTA DIDIK YANG MEMILIKI PRESTASI BELAJAR TINGGI DAN KEMAMPUAN EKONOMI RENDAH - Ervin, Oknilia; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This problems based onÂ  learners who has low economy capacity but has high academic achievement in study, different with learners who has high economy, but ignore to its academic achievement to learn. This research intend to describe 1) Learnerâs profil who has high academic achievement andÂ  low economy capacity seen from cognitive aspect. 2) Profil of student who has high academic achievement and low economy capacity seen from psychomotor. 3) Profil of student who has high academic achievement and low economy capacity seen from effective aspect. This Research was descriptive qualitative research consists of learnerâs informant, teacher, adviser, coordinator of conseling, counselor and lear nerâs parent. Data were collected through interview and documentation. The result of this research describe that : 1) learner who has high academic achievement and low economy capacity seen from the aspect cognitive described that when a teacher explaine the subject material student pay attention seriously, high motivation, and able to observing, understanding, and analyzing each subjects. 2) learner who has high academic achievement and low economy capacity seen from psychomotor, able to utilize facilities to learn well. 3) from effective aspect learner who has high academic achievement and low economy capacity has good characters, attitude, polite, and loyal to religion.